Spectrophotometric and Conductometric Determination of Clomiphene Citrate and Nefazodone HCl - Wafaa S. Hassan; Mervat M. Hosny (E-Journal of Chemistry)
Two accurate, rapid and simple spectrophotometric and conductometric methods were developed for the determination of clomiphene citrate (CMP) and nefazodone HCl (NFZ), the proposed methods depends upon the reaction of ammonium reineckate with the two studied drugs to form stable precipitate of ion-pair complexes, which was dissolved in suitable solvent. The pink colored complexes were determined colorimetrically at 509, 523.6 nm, respectively. Using the conductometric titration, the studied drugs could be evaluated in 50% (v/v) acetone in the range 60.02-540.18 and 63.3-443.1 μg mL-1 for clomiphene citrate and nefazodone HCl, respectively. While for spectrophotometric method the ranges were 0.2-1.8 and 0.2-1.6 mg mL-1 for clomiphene citrate and nefazodone HCl respectively. Various experimental conditions were studied. The results obtained showed good recoveries with relative standard deviations of 0.759 and 0.552%. The proposed procedures were applied successfully to the analysis of these drugs in their pharmaceutical preparations and the results were favourably comparable with the official and reference methods. The molar combining ratio reveal that (1:1) (drug : reagent) ion associates were formed.